KAJIAN PERMAKANAN TARUNA DI SEKOLAH TINGGI PENERBANGAN INDONESIA - Endang Sugih Arti.; Erwin Kurniadi; Rini Sadiatmi (Langit Biru: Jurnal Ilmiah Aviasi, 2017)
Endang Sugih Arti,SE,M.Si, Erwin Kurniadi,S.SiT,ST,MM and Rini Sadiatmi,S.Pd,M.Si, Research : The Study of Student Food at Indonesian Aviation Training Institute Curug Tangerang, July 2016. The aim of this research is to know about condition of student food at Indonesian Aviation Training Institute Curug Tangerang , the research method is descriptive analyses and collecting data by documentation , observation, interview, book study and questionaire